2009
DOI: 10.1002/cphc.200800626
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on the Electronic States and O‐Loss Photodissociation of the NO2+ Ion

Abstract: CASPT2 (multiconfiguration second-order perturbation theory) calculations were performed at the molecular geometry for 17 low-lying singlet and triplet states of the NO(2)(+) ion. The CASPT2 vertical relative energies (T(v)') were obtained and the characters of these ionic states (primary or shake-up ionization states) were determined. For the eight low-lying states, we performed CASPT2 geometry optimization calculations and obtained the CASPT2 adiabatic relative energies (T(0)). We conclude that the 1(1)A(1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 27 publications
6
16
0
Order By: Relevance
“…It is known that the complete active space self‐consistent field (CASSCF) 12 and multiconfiguration second‐order perturbation theory (CASPT2) 13, 14 methods are effective for theoretical studies of excited electronic states of molecules and molecular ions 1, 15–17. We have carried out large‐scale calculations for some low‐lying doublet electronic states of the C 6 H 5 Br + ion using the CASSCF and CASPT2 methods.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the complete active space self‐consistent field (CASSCF) 12 and multiconfiguration second‐order perturbation theory (CASPT2) 13, 14 methods are effective for theoretical studies of excited electronic states of molecules and molecular ions 1, 15–17. We have carried out large‐scale calculations for some low‐lying doublet electronic states of the C 6 H 5 Br + ion using the CASSCF and CASPT2 methods.…”
Section: Introductionmentioning
confidence: 99%
“…This process may be interpreted as an ionisation into vibrationally excited NO2 + (X 1 g,1, 2, 3) followed by quasi-resonant dissociation with no excess of energy to the ground state limit L1 (NO + (X 2 ), O( 3 P)). We note that such a reaction necessarily involves an intersystem crossing mechanism 21 . Large spin-orbit coupling values are indeed found in the CASPT2 calculations 21 in particular between the NO2 + (X 1 1) and (a 3 B2) ionic states.…”
Section: A Electron-ion Kinetic Energy Correlationmentioning
confidence: 99%
“…We note that such a reaction necessarily involves an intersystem crossing mechanism 21 . Large spin-orbit coupling values are indeed found in the CASPT2 calculations 21 in particular between the NO2 + (X 1 1) and (a 3 B2) ionic states.…”
Section: A Electron-ion Kinetic Energy Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the CASSCF (complete active space self‐consistent field)27 and CASPT2 (multiconfiguration second‐order perturbation theory)28, 29 methods are effective for theoretical studies of excited electronic states of molecules and molecular ions 30–33. Recently, we34 studied the HBeN − radical anion and its isomer HNBe − which, being isoelectronic to the HBO + and HOB + cations, by using CASSCF and CASPT2 methods and found that a bending local minimum M1 along the 1 2 A′′ potential energy surface and the A 2 Π state of HNBe − should be the transition state of the isomerization reactions for M1↔ M1.…”
Section: Introductionmentioning
confidence: 99%